(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Myofunctional appliance are considered by many authorities orthopedic in nature, influencing the facial skeleton of the growing child in the condylar and suture areas. They also exert an orthodontic effect on the dent-alveolar area. Among these activator is the most well-known myofunctional appliance. The article describes the myofunctional appliance and its technique training, design, steps in preparation of Class II and Class III activator in sequential stages with illustrated case reports, treating class III molar relationship with crowded arch in maxilla and anterior cross bite. The Author acknowledges that the article is summarized from the lectures, handouts during his postgraduate studies in Kyushu University and Hiroshima University, Japan and from his experience from Dhaka Dental College and private practice at Ortho Dental Care. This article is a continuation of the series of technique training in orthodontics especially for the post-graduate trainees as well as for the practitioners who will learn and practice functional appliance specially activators. Once again, I believe that post-graduate trainee doctors, faculty members, private practitioners and all other concerned will find this article as a guide line during their training as well as in their professional practicing period. DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.16003 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 34-46